(untitled) (Economics and region, 2021)
The purpose of the article is to study the analysis of brand positioning in the hotel and restaurant business in the Poltava region. The article considers the stages that hotels go through in the process of using the brand in their own activities. It is established that the brand becomes an integrated combination of the impression it makes on consumers and the result of their experience in using the product and contains 4 key aspects from the point of view of enterprises. The main task of branding of the hotel and restaurant business is the formation and further development of positive consumer associations associated with its brand. The study found that among the many factors and factors influencing the effectiveness of the hotel business, the problems of positioning the hotel brand are important. The article discusses the concept of branding in the hotel and restaurant business, also conducted a comparative analysis of the rating hotels in Poltava, the number of accommodation and pricing policy of standard rooms, identified the efficiency and benefits of chain hotels.